2017
DOI: 10.1111/1756-185x.13205
|View full text |Cite
|
Sign up to set email alerts
|

Generalised joint hypermobility and knee joint hypermobility: prevalence, knee joint symptoms and health‐related quality of life in a Danish adult population

Abstract: GJHk and KJH were frequently reported in the Danish adult population, mostly in women. Respondents with GJHk and KJH were two times more likely to report knee joint-related symptoms such as pain, reduced performance of usual activity and lower HRQoL. The impact of these conditions on HRQoL is comparable with knee osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 45 publications
2
20
0
1
Order By: Relevance
“…Using patient-reported outcome measurements is important in order to quantify patient satisfaction. The subgroup of patients with GJH are already at a disadvantage preinjury, as is illustrated by a recent study of 1006 non-injured Danish adults demonstrating that patients with GJH or knee joint hypermobility had a twofold probability of reporting symptoms such as knee pain, inferior performance of usual activity and reduced health-related quality of life 15. It is therefore especially important to optimise both surgical interventions and rehabilitation in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using patient-reported outcome measurements is important in order to quantify patient satisfaction. The subgroup of patients with GJH are already at a disadvantage preinjury, as is illustrated by a recent study of 1006 non-injured Danish adults demonstrating that patients with GJH or knee joint hypermobility had a twofold probability of reporting symptoms such as knee pain, inferior performance of usual activity and reduced health-related quality of life 15. It is therefore especially important to optimise both surgical interventions and rehabilitation in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of GJH ranges from 2% to 57%, depending on the definition and methods used 11–14. A large, recent study of a general Danish population found that the self-reported prevalence of GJH and knee joint hypermobility was 13% and 23%, respectively 15. GJH is more common in young persons and in females and the prevalence varies with ethnic background 11.…”
Section: Introductionmentioning
confidence: 99%
“…This 1‐year retrospective case control study suggests the prevalence of G‐HSD is higher in the myofascial pelvic pain population than the general population although the precise prevalence of G‐HSD in the general population is unknown, partially because of the new nosology of HSD. Joint hypermobility alone is thought to be very common in the general population, affecting approximately 6% to 57% of individuals to some degree; however, this includes all individuals on the joint hypermobility spectrum, even those with single hypermobile joints . The prevalence of JHS, or chronic musculoskeletal pain due to joint hypermobility, is not firmly established with estimates ranging from 3% to 20% of women in the general population …”
Section: Discussionmentioning
confidence: 99%
“…Joint hypermobility alone is thought to be very common in the general population, affecting approximately 6% to 57% of individuals to some degree; however, this includes all individuals on the joint hypermobility spectrum, even those with single hypermobile joints. 37,38 The prevalence of JHS, or chronic musculoskeletal pain due to joint hypermobility, is not firmly established with estimates ranging from 3% to 20% of women in the general population. [21][22][23] We were surprised to find such low numbers of patients with provoked vestibulodynia as determined by Q-tip test in both the case and control groups despite a significantly higher percentage of patients reporting dyspareunia, as the two conditions are generally highly associated.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37][38][39][40][41][42][43][44][45] The morbidity of hEDS/HSD to patients is most commonly expressed as complaints to clinicians of chronic musculoskeletal pain, headache and fatigue. These symptoms impair physical activity and quality of life [34][35][36][37][38][39][40][41][42][43][44][45] , common to both FIbromyalgia and ME/CFS. In rheumatology clinics, symptomatic hypermobility is estimated to contribute to nearly half of all outpatient appointments, but is only recognised 1 out of 19 times 46 .…”
Section: Introductionmentioning
confidence: 99%